2016
DOI: 10.1016/j.ijpsycho.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Test-retest reliability of a single-channel, wireless EEG system

Abstract: Recording systems to acquire electroencephalogram (EEG) data are traditionally lab-based. However, there are shortcomings to this method, and the ease of use and portability of emerging wireless EEG technologies offer a promising alternative. A previous validity study demonstrated data derived from a single-channel, wireless system (NeuroSky ThinkGear, San Jose, California) is comparable to EEG recorded from conventional lab-based equipment. The current study evaluated the reliability of this portable system u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(79 citation statements)
references
References 58 publications
5
72
0
2
Order By: Relevance
“…Several studies in the last years demonstrated significant results to use NeuroSky device in various researches . These are dry electrodes that can measure brainwaves millimeters from the scalp and thus can easily be worn over hair.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies in the last years demonstrated significant results to use NeuroSky device in various researches . These are dry electrodes that can measure brainwaves millimeters from the scalp and thus can easily be worn over hair.…”
Section: Methodsmentioning
confidence: 99%
“…(2009) suggest that the NeuroSky's MindSet provides accurate readings regarding attention, since there is a positive correlation between measured and selfreported attention levels. Another team of researchers (Rogers at al., 2016) evaluated the reliability of such single-channel, wireless EEG portable system using test-retest and reliable change analyses. They concluded, that a portable device may provide a viable alternative to conventional lab-based recording systems for assessing changes in electrophysiological signals, and further application to the study of brain function using the system can be encouraged.…”
Section: Methodsmentioning
confidence: 99%
“…A previous validation study demonstrated that data derived from a single channel, the wireless system (NeuroSky Mind-Wave) is comparable to EEG recorded from conventional labbased equipment. However, critical open issues (e.g., real-time, quality of recordings) remain yet unexplored [3]. One of the unexplored aspects is the electrode placement, which in most EEG devices is fixed depending on the targeted application/s.…”
Section: Introductionmentioning
confidence: 99%
“…However, the conditions are not directly comparable because the first device uses wetelectrodes while the second one uses dry electrodes. It is well 2 14 128 Hz Wet EMOTIV Insight 3 5 128 Hz Dry Muse 4 5 256 Hz Dry Neurosky MindWave 5 1 512 Hz Dry known that wet electrodes have problems for real-time/longterm use. Most EEG devices available in the market were tailored designed for a set of tasks and neuro-paradigms and in general, they are found to be reliable only within those tasks and neuroparadigms.…”
Section: Introductionmentioning
confidence: 99%